2016
DOI: 10.1016/j.apjtm.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-tubercular activity of linolenic acid and conjugated-linoleic acid as effective inhibitors against Mycobacterium tuberculosis

Abstract: These results demonstrate that linolenic acid and CLA not only have effective anti-Mtb activity/properties, but also induce the selective-anti-Mtb effects by strongly inhibiting and blocking the growth/proliferation of Mtb through a new pharmacological activity/action. Therefore, this study provides novel perspectives for the effective use of them and the potential that can be used as potent anti-Mtb candidate drugs, as well as suggests the advantage of reducing the cost and/or time for developing a new/substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Furthermore, lauric acid (10) exhibited antidiabetic [51] and antibacterial [52] activities. Simultaneously, linoleic acid (16), polyunsaturated fatty acid, presents antimicrobial [53] and anti-inflammatory activities, [54] and is also involved in the synthesis of prostaglandins, thromboxanes and leukotriene. [55] In conclusion, the two studied halophytic grasses seem to be rich in fatty acids, especially in saturated fatty acids.…”
Section: Fatty Acids and Their Ester Derivativesmentioning
confidence: 99%
“…Furthermore, lauric acid (10) exhibited antidiabetic [51] and antibacterial [52] activities. Simultaneously, linoleic acid (16), polyunsaturated fatty acid, presents antimicrobial [53] and anti-inflammatory activities, [54] and is also involved in the synthesis of prostaglandins, thromboxanes and leukotriene. [55] In conclusion, the two studied halophytic grasses seem to be rich in fatty acids, especially in saturated fatty acids.…”
Section: Fatty Acids and Their Ester Derivativesmentioning
confidence: 99%
“…[58,59] In addition, Linolenic acid was also present in the extract of Khalas date, a research demonstrated that linoleic acid effectively inhibited Mycobacterium tuberculosis. [60] ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, linoleic acid ( 50 ), another polyunsaturated fatty acid, is involved in the synthesis of prostaglandins, thromboxanes and leukotriene, a fact recognized over the last century [76]. Several studies have also reported its antimicrobial [77] and anti-inflammatory activities [78].…”
Section: Phytoconstituents Of Halophytic Grassesmentioning
confidence: 99%